RELEVANSI KONSEP PEMISAHAN HARTA DALAM PERJANJIAN PERKAWINAN DI INDONESIA (STUDI LITERATUR PMK NO. 69/PUU-XIII/2015 DAN KHI) - Muhammad Nabih Ali (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2023)
Decision of the Constitutional Court Number 69/PUU-XIII/2015 and the Compilation of Islamic Law is one of the main foundations in marriage negotiations. MK Decision No. 69/PUU-XIII/2015 becomes a forum for positive law, and the Compilation of Islamic Law becomes an interpretation that makes it easier for people to understand marriage agreements in accordance with Islamic law. The purpose of this study was to determine the relevance and legal consequences of the Constitutional Court Decision Number 69/PUU-XIII/2015 and the Compilation of Islamic Law regarding marriage agreements. This research method uses normative juridical, with a traditional review approach to analyze data. The results of this study indicate, 1) The relevance of the two rules, namely the Constitutional Court Decision Number 69/PUU-XIII/2015 and the Compilation of Islamic Law have the same goal, namely to have a positive impact on households. The agreement was also made as an effort to respond to negative impacts if a bad possibility occurs, namely divorce in the household. 2) Separation of assets that are part of the marriage agreement is permissible as long as it does not conflict with applicable law. The legal consequences proposed in the marriage agreement, if the agreement is made according to the applicable provisions, then it has binding consequences and must be obeyed.